Profil Pendidikan Politisi terhadap Kinerja di DPRD Provinsi Sumatera Selatan - Kariem, Muhammad Quranul; Sabillah (Jurnal Pemerintahan dan Politik, 2024)
This article discusses the educational background of members of parliament in the field of government studies, political science, or public administration related to their performance in government management, specifically in the area of oversight functions. The method used is literature review, analyzing and drawing conclusions from credible secondary data sources. The research findings indicate that the educational background of new politicians is limited to formal academic degrees and has not yet significantly impacted the implementation of effective oversight functions in government management. However, politicians do understand their roles and responsibilities as members of the council. The recommendation from this study is the appropriate use of information technology to provide transparent and accountable information on the execution of oversight functions to the public